Identifying contextual predictors of urban park utilization among inter-ethnic groups in Malaysia - Elfartas, Hesham Omran; Albeera, Haithem Ahmed; Said, Ismail; Momoh, Job U. (Journal of Architecture and Urbanism, 2019)
Social interaction among diverse ethnic groups motivates people within communities to visit urban parks towards achieving social cohesion. Malaysians of different ethnic backgrounds spend their leisure time in urban parks because it offers opportunities for social interaction. The perception and requirement of attributes needed varies among the various ethnic groups of Malays, Chinese and Indians in order to be assured of their full utilization of the parks. This study investigates the urban park attributes that encourage the utilization of urban park by these three ethnic groups toward achieving social cohesion. Using a survey questionnaire method a total of 274 respondents were sampled at Batu Pahat urban parks in Johor, Malaysia. Afterwards, Structural Equation Modelling (SEM) was used to analyse and validate respondents’ perception of urban park utilization. The findings show that aesthetics, safety, lighting, maintenance and cleanliness in public spaces attracted people to visit the urban park and contributed towards social cohesion.